2013
DOI: 10.1117/12.2030481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of material response in fused silica and KDP following exit surface laser- induced breakdown

Abstract: Crater formation that accompanies laser-induced damage is the result of material ejection following the rapid, localized heating to temperatures on the order of 1 eV. The objective of this work is to compare the material ejection behavior in fused silica and KDP crystals as captured using time-resolved shadowgraphy. These two materials are of fundamental importance in ICF class laser systems but they also represent materials with significantly different physical properties. We hypothesize that these different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This phenomenon is consistent with the liquid ejection behavior experimentally observed in the laser damage processes reported in refs. 37,38 . As the material properties of high-temperature phase transition region are affected by multiple physical parameters such as temperature, pressure, ionization and so on, a small parameter change would incur a huge impact on the morphology of laser damage crater.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is consistent with the liquid ejection behavior experimentally observed in the laser damage processes reported in refs. 37,38 . As the material properties of high-temperature phase transition region are affected by multiple physical parameters such as temperature, pressure, ionization and so on, a small parameter change would incur a huge impact on the morphology of laser damage crater.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore the magnitude and effect of stress more concisely, Zeng et al [94] conducted further investigation and found a second wave would be generated inside the fused silica due to the high back-pressure of the laser-generated plasma, as shown in Figure 19b. In addition, Demos et al [95] explored and compared the kinetic behavior of KDP and fused silica under laser irradiation. It is clear that the expansion of shockwaves in air in Figure 19a is quite similar in both materials at the same delay time, which also suggests that the initial energy deposited in a single laser-induced breakdown event was roughly the same.…”
Section: Exploration Of Transient Behavior At the Initiation Of Damagementioning
confidence: 99%
“…It is clear that the expansion of shockwaves in air in Figure19a is quite similar in both materials at the same delay time, which also suggests that the initial energy deposited in a single laser-induced breakdown event was roughly the same. [95]. c1 The distribution of thermal stress due to temperature gradient and expansion; c2 The deformation of crystal materials under tensile stress [87].…”
Section: Exploration Of Transient Behavior At the Initiation Of Damagementioning
confidence: 99%
See 2 more Smart Citations